Efektivitas Terapi Topikal Oksigen Luka Dalam Penyembuhan Luka Diabetic Foot Ulcers: Literature Review - Khairul Bahri; Rizki Hidayat; Naziyah Naziyah (Universitas Malahayati Lampung, 2024)
ABSTRACT Considered the main cause of motility and morbidity of lower extremity amputation rates, diabetic ulcers are considered to be the aetiology of neuropathy, ischemia, and neuro ischemia. According to the study, the global DFU frequency was 6.3%, with the highest prevalence of 13% in the United States. After twelve weeks, fifty-two per cent of the new DFUs were not cured. DFU failure to heal can lead to serious problems such as injuries and amputations, maintenance costs, health costs, and even death due to DFU complications. Therefore, the global goal is the use of appropriate care for enhanced wound healing in DFU. Oxygen is essential for the wound-healing process. Providing adequate oxygen to the wound area helps the healing process. Oxygen improves cell metabolism, energy production, collagen formation, immune cell activation, infection reduction, new blood vessel formation, and is anti-inflammatory. To see the effectiveness of topical wound oxygen in healing diabetic foot ulcers. Systematics review, through a systematic search of four databases (EMBASE, MEDLINE, PubMed, ScienceDirect). Published from 2017 to 2023, of the 25 references that have been identified, there are 25 that are carefully examined in detail. Of these, there are four research references that meet the criteria for inclusion and exclusion, all of which contain instruments relevant to the variables in the systematics of this review. From the four references used, the results showed topical therapy of wound oxygen in wound healing was effective in the treatment of diabetic foot ulcers. The combination of topical wound oxygen and standard care helps speed up the wound healing process within 12 weeks. The addition of topical adjuvants of wound oxygen as the gold standard of diabetic foot ulcer wound care helps patients with hard-to-heal DFU close wounds faster. Keyword: Topical Wound Oxygen, Wound Healing, Diabetic Foot Ulcers ABSTRAK Dianggap sebagai penyebab utama motalitas dan morbiditas angka amputasi ekstermitas bawah, diabetes ulcers dianggap sebagai etiologi neuropati, iskemia, dan neuroiskemia. Menurut penelitian, frekuensi DFU global sebesar 6,3%, dengan revalensi tertinggi 13% di Amerika Serikat.Setelah dua belas minggu, lima puluh dua persen DFU baru tidak sembuh. Kegagalan kesembuhan DFU dapat menyebabkan masalah serius seperti luka dan amputasi, biaya perawatatan, biaya kesehatan, dan bahkan kematian akibat komplikasi DFU. Oleh karena itu, tujuan global adalah penggunaan perawatan yang tepat dalam penyembuhan luka yang ditingkatkan pada DFU. Oksigen sangat penting untuk proses penyembuhan luka. Penyediaan oksigen yang cukup ke area luka membantu proses penyembuhan. Oksigen meningkatkan metabolisme sel, produksi energi, pembentukan kolagen, aktivasi sel kekebalan, pengurangan infeksi, pembentukan pembuluh darah baru, dan antiinflamasi. Untuk melihat efektivitas topikal oksigen luka dalam penyembuhan luka diabetic foot ulcer. Sistematika review, melalui penelusuran secara sistematik pada empat database (EMBASE, MEDLINE, PubMed, ScienceDirect). Yang dipublikasi sejak tahun 2017 – 2023, dari 25 jumlah referensi yang telah diidentifikasi, ada 25 referensi yang diperiksa dengan teliti dengan detail, dari jumlah tersebut, terdapat 4 referensi penelitian yang memenuhi kriteria inlkusi dan ekslusi, dimana seluruhnya memuat instrument yang relevan dengan variable pada sistematika review ini. Dari empat referensi yang digunakan hasilnya menunjukkan terapi topical oksigen luka dalam penyembuhan luka sanagt efektif dalam perawatan diabetic foot ulcer. Kombinasi topical oksigen luka dan standar perawatan uka sangat membantu mempercepat proses penyembuhan luka dalam waktu 12 minggu. Penambahan adjuvan topikal oksigen luka sebagai gold standar perawatan luka diabetic foot ulcer membantu pasien dengan DFU yang sulit disembuhkan menutup luka lebih cepat. Kata Kunci: Topikal Oksigen Luka, Penyembuhan Luka, Diabetic Foot Ulcers